2022
DOI: 10.1037/hea0001120
|View full text |Cite
|
Sign up to set email alerts
|

Race, trust, and COVID-19 vaccine hesitancy in people with opioid use disorder.

Abstract: Objective: Vaccination against coronavirus disease 2019 (COVID-19) is a promising avenue for arresting the COVID-19 pandemic, yet suboptimal rates of vaccine uptake in at-risk groups may hinder efficacy and worsen existing health disparities. People with opioid use disorder (OUD) are likely to face increased vulnerability to COVID-19 due to a confluence of biological and social risk factors. We sought to assess factors associated with willingness to vaccinate against COVID-19 in people with OUD. Method: Phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Previous studies on vaccine intentions related to the COVID‐19 vaccine in developed countries showed an acceptance rate of less than half among people with OUD, mainly related to concerns about vaccine safety [ 17 , 18 , 19 ]. The higher vaccination rates in this study may be explained by the fact that people were engaged in opioid agonist therapy, which is a factor that has been associated with increased uptake of other vaccines among people with OUD [ 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on vaccine intentions related to the COVID‐19 vaccine in developed countries showed an acceptance rate of less than half among people with OUD, mainly related to concerns about vaccine safety [ 17 , 18 , 19 ]. The higher vaccination rates in this study may be explained by the fact that people were engaged in opioid agonist therapy, which is a factor that has been associated with increased uptake of other vaccines among people with OUD [ 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they are a population characterised by low‐estimated vaccination coverage for other recommended vaccines, including pneumococcal, diphteria, tetanus and pertussis vaccine, hepatitis A, hepatitis B and influenza [ 14 , 15 , 16 ]. In the case of the COVID‐19 vaccine, previous studies regarding the vaccine roll‐out in developed countries have shown a high prevalence of hesitancy among people with SUD [ 17 , 18 , 19 ]. Data from an Australian National Drug Surveillance System showed that only 57% of the people who inject drugs would definitely or probably receive a COVID‐19 vaccine if available, which was significantly lower than the 77% observed in the broader Australian population [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unable to leave their animals unattended, pet owners chose to forego their own health, often saying "pet before self". 1 , 6 SVO's Advantage: Capitalizing on the Human/Pet Bond and a Trusting Relationship Research literature has repeatedly identi ed trust as the key component to a strong, positive patient/provider relationship 8,9 . Patients who trust their care providers are more likely to follow medical advice and seek support.…”
Section: Bene Ts and Barriers Of Animal Companions For Those Who Are ...mentioning
confidence: 99%
“…Indeed, in the last couple of years, this has been seen most clearly in the realm of COVID-19 information. The widespread, often con icting information on the disease, who it impacts, the veracity of the vaccines and what evidence is a reliable guide to addressing the pandemic has created confusion and reluctance in a large portion of our society [8][9][10] . People of color, those who have historically suffered from racial injustices in the healthcare system, have been overwhelmingly reticent about medically endorsed COVID-19 safety precautions and vaccinations [11][12][13] .…”
Section: Bene Ts and Barriers Of Animal Companions For Those Who Are ...mentioning
confidence: 99%